Integrating neuroscientific knowledge into psychotherapy amongst Japanese psychotherapists: presence, benefits, needs and cultural barriers. (2nd January 2022) - Takizawa, Yu; Murray, Judith; Bambling, Matthew; Matsumoto, Yuki; Ishimoto, Yuma; Yamane, Takahiro; Edirippulige, Sisira
ABSTRACT: The practice of neuroscience-informed psychotherapy (NIP) that aims to refine the existing practice of psychotherapy is a recent topic in psychotherapy research. The researcher interviewed 25 Japanese psychotherapists and investigated the presence, benefits and needs of NIP and the potential barriers that may hinder the learning of NIP. A thematic analysis identified that the practice of NIP is currently limited in Japan due to limited learning opportunities. However, a minor proportion of Japanese psychotherapists practice NIP and experienced benefits, such as developing confidence in performing psychotherapy and effectively guiding clients to normalize problems. NIP may benefit psychotherapists in Japan and other Asian countries as psychotherapy in Japan and other Asian countries share many characteristics influenced by Confucianism, Buddhism and Westernization.